Sociodemographic risk factors for coronavirus disease 2019 (COVID-19) infection among Massachusetts healthcare workers: A retrospective cohort study - Lan, Fan Yun; Filler, Robert; Mathew, Soni; Buley, Jane; Iliaki, Eirini; Bruno-Murtha, Lou Ann; Osgood, Rebecca; Christophi, Costas A.; Fernandez-Montero, Alejandro; Kales, Stefanos N. (My University, 2021)
Objective: To better understand coronavirus disease 2019 (COVID-19) transmission among healthcare workers (HCWs), we investigated occupational and nonoccupational risk factors associated with cumulative COVID-19 incidence among a Massachusetts HCW cohort. Design, setting, and participants: The retrospective cohort study included adult HCWs in a single healthcare system from March 9 to June 3, 2020. Methods: The SARS-CoV-2 nasopharyngeal RT-PCR results and demographics of the study participants were deidentified and extracted from an established occupational health, COVID-19 database at the healthcare system. HCWs from each particular job grouping had been categorized into frontline or nonfrontline workers. Incidence rate ratios (IRRs) and odds ratios (ORs) were used to compare subgroups after excluding HCWs involved in early infection clusters before universal masking began. A sensitivity analysis was performed comparing jobs with the greatest potential occupational risks with others. Results: Of 5,177 HCWs, 152 (2.94%) were diagnosed with COVID-19. Affected HCWs resided in areas with higher community attack rates (median, 1,755.2 vs 1,412.4 cases per 100,000; P < .001; multivariate-adjusted IRR, 1.89; 95% CI, 1.03–3.44 comparing fifth to first quintile of community rates). After multivariate adjustment, African-American and Hispanic HCWs had higher incidence of COVID-19 than non- Hispanic white HCWs (IRR, 2.78; 95% CI, 1.78–4.33; and IRR, 2.41, 95% CI, 1.42–4.07, respectively). After adjusting for race and residential rates, frontline HCWs had a higher IRR (1.73, 95% CI, 1.16–2.54) than nonfrontline HCWs overall, but not within specific job categories nor when comparing the highest risk jobs to others. Conclusions: After universal masking was instituted, the strongest risk factors associated with HCW COVID-19 infection were residential community infection rate and race.
Keywords: Nasopharyngeal Swabs; Serologic Tests; COVID-19